'You can't arrest a virus': The freedom of expression crisis within Egypt's response to COVID-19. (1st June 2021) - Cosentino, Gabriele
The article discusses the freedom of expression crisis that characterized the authoritarian response of the Egyptian government to the COVID-19 pandemic. Through the case study of the expulsion of the foreign correspondent for The Guardian over contested outbreak data, the article argues that authorities in Egypt exploited the pandemic for political ends by silencing critics and by manipulating the public opinion.